BUZANO’S INEQUALITY IN ALGEBRAIC PROBABILITY SPACES - Agredo, J.; Leon, Y.; Osorio, J.; Peña, A. (Croacia, 2019)
We obtain a generalization of Buzano’s inequality of vectors in Hilbert spaces , using the theory of algebraic probability spaces. In particular, we extend a result of Dragomir given in [7]. Applications for numerical inequalities for n- tuples of bounded linear operators and functions of operators defined by double power series are also generalized.

Obtenemos una generalización de la desigualdad de Buzano de vectores en espacios de Hilbert , utilizando la teoría de los espacios algebraicos de probabilidad. En particular, extendemos un resultado de Dragomir dado en [7]. Aplicaciones para desigualdades numéricas para n-tuplas de operadores lineales acotados y funciones de operadores definidos por series de potencias dobles también se generalizan. Traducción realizada con la versión gratuita del traductor www.DeepL.com/Translator
Keywords: Buzano’s inequality; Algebraic probability spaces; Desigualdad de Buzano; Espacios algebraicos de probabilidad.